Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/bpa.12903
|View full text |Cite
|
Sign up to set email alerts
|

Aged Tmem106b knockout mice display gait deficits in coincidence with Purkinje cell loss and only limited signs of non‐motor dysfunction

Abstract: Genetic variants in TMEM106B are a major risk factor for several neurodegenerative diseases including frontotemporal degeneration, limbic-predominant age-related TDP-43 encephalopathy, Parkinson's disease, late-onset-Alzheimer's disease and constitute a genetic determinant of differential aging. TMEM106B encodes an integral lysosomal membrane protein but its precise physiological function in the central nervous system remains enigmatic. Presently, we aimed to increase understanding of TMEM106B contribution to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 53 publications
(82 reference statements)
7
15
0
Order By: Relevance
“…This analysis showed that the loss of Tmem106b results in an approximately 2‐fold increase of immunoreactivity of Gfap ( p < 0.01) and Iba‐1 ( p < 0.05) in the cerebellum as compared to WT mice (Figure 1F–H). Similar to the observation from Stroobants et al (1), gliosis was pronounced in the molecular layer and white matter tract. We also observed that there were significantly more lysosomal enlarged Purkinje neurons and microglia cells in Tmem106b−/− as compared to WT mice as evidenced by Lamp1 immunofluorescence staining (Figure S1).…”
Section: Figuresupporting
confidence: 89%
See 4 more Smart Citations
“…This analysis showed that the loss of Tmem106b results in an approximately 2‐fold increase of immunoreactivity of Gfap ( p < 0.01) and Iba‐1 ( p < 0.05) in the cerebellum as compared to WT mice (Figure 1F–H). Similar to the observation from Stroobants et al (1), gliosis was pronounced in the molecular layer and white matter tract. We also observed that there were significantly more lysosomal enlarged Purkinje neurons and microglia cells in Tmem106b−/− as compared to WT mice as evidenced by Lamp1 immunofluorescence staining (Figure S1).…”
Section: Figuresupporting
confidence: 89%
“…We also demonstrated that Tmem106b deficiency results in lysosomal enlargement in both Purkinje cells and microglia, and increased neuro-inflammation including complement system activation. Together with the independent findings from Stroobants et al (1), these data suggest that, in addition to myelination (8), Tmem106b also plays important role in maintaining the health and survival of cerebellar Purkinje cells during aging.…”
Section: Loss Of Tmem106b Leads To Cerebellum Purkinje Cell Death and Motor Deficitssupporting
confidence: 72%
See 3 more Smart Citations